POLIGAMI DALAM PERSPEKTIF USHUL Al-FIQH - Iim Fahimah (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2017)
Abstract: In the Qur’an, the issue of polygamy is only mentioned in verses 3 and verse 129. In verse 3 talks about the permissibility of polygamy, in verse 129 it talks about the difficulty and inability of a husband to do justice to wives. This means that the permissibility of polygamy is bound by strict conditions which means if the condition is not met, then polygamy should not be done. In the perspective of ushul fiqh to be reviewed is the polygamy verse which includes amr shigat and its legal implications and ta’arud al-adillah in the polygamy verse related to fair terms for polygamy perpetrators against his wives. The three editors used in the Qur’an are the orders of marrying women -women are considered good, so scholars differ when giving the meaning of the verse. Some say a maximum of 4, there are 8, there is also a limit of 16. Furthermore scholars also differed whether the rukhsah one, or more than one. In this case, the author is more likely to say that polygamy is rukhsah, while his azimah remains one. Polygamy is permissible if the situation requires polygamy, but if with monogamy there is no problem, then monogamy is better.